Relationship between Dehydroepiandrosterone Sulfate and Ischemic Heart Disease in Men - Jawad, Shaimaa Mahdi A.; Al-Obaidi, Sabah A.R.; Al-Sultani, Yahya K. (Al-Kufa University Journal for Biology, 2010)
Thirty two patients with ischemic heart disease (aged 40- 69 years) involved in this study during their admission Ibn-Albitar, Ibn-Alnafees Hospitals Baghdad and theIraqiCenterfor Heart Surgery,MedicalCity. Age matched twenty seven healthy men also included as control group. The results obtained are: serum triglycerides (TG) and very low density lipoprotein (VLDL) shows a significant (p<0.05) increase in patients with I.H.D as compared with control group in age range 50-59 years. As well as, no significant correlation was found in I.H.D and control groups between dehydroepiandrosterone sulfate (DHEA-S) and lipid profile, although there was a slight negative correlation between DHEA-S levels and each of TG and VLDL in I.H.D group.